2014
DOI: 10.1088/0957-4484/25/45/455703
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and electronic properties of monolayer and bilayer phosphorene under uniaxial and isotropic strains

Abstract: The mechanical and electronic properties of both the monolayer and bilayer phosphorenes under either isotropic or uniaxial strain have been systematically investigated using first-principles calculations. It is interesting to find that: 1) Under a large enough isotropic tensile strain, the monolayer phosphorene would lose its pucker structure and transform into a flat hexagonal plane, while two inner sublayers of the bilayer phosphorene could be bonded due to its interlayer distance contraction. 2) Under the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 21 publications
4
89
0
Order By: Relevance
“…An adventitious strain is almost unavoidable experimentally, therefore, it is highly desirable to explore the mechanical properties of borophene.For 2D materials, the ideal tensile strength [10,11], is a crucial mechanical parameter which fundamentally characterizes the nature of the chemical bonding and the elastic limit of the single-or few-layer thin films. So far, the elastic limit of many 2D materials, such as graphene [12][13][14], h-BN [15][16][17][18][19], MoS 2 [20-24], black phosphorene (BP) [25][26][27][28], and silicone [29][30][31][32][33], have been characterized by the ideal tensile stress and critical strain. Compared to these materials, monolayer borophene is a stiffer material because of a higher Young's Modulus [7].…”
mentioning
confidence: 99%
“…An adventitious strain is almost unavoidable experimentally, therefore, it is highly desirable to explore the mechanical properties of borophene.For 2D materials, the ideal tensile strength [10,11], is a crucial mechanical parameter which fundamentally characterizes the nature of the chemical bonding and the elastic limit of the single-or few-layer thin films. So far, the elastic limit of many 2D materials, such as graphene [12][13][14], h-BN [15][16][17][18][19], MoS 2 [20-24], black phosphorene (BP) [25][26][27][28], and silicone [29][30][31][32][33], have been characterized by the ideal tensile stress and critical strain. Compared to these materials, monolayer borophene is a stiffer material because of a higher Young's Modulus [7].…”
mentioning
confidence: 99%
“…Recent computational studies based on the density functional theory (DFT) showed that a single-layer phosphorene could actualize tensile strain (stretching) up to 0.54 while maintaining its original P-P bond and “two-sublayer” (non-planar) structure2728. It has also been demonstrated that all the electrical29303132, optical3334, thermoelectric353637 and mechanical273038 properties of phosphorene could be modified upon mechanical strain. The puckered structure of phosphorene brings anisotropy and negative Poisson’s ratio2735.…”
mentioning
confidence: 99%
“…Due to the buckled structure of phosphorene, the direction and type of applied mechanical strain would affect the magnitude of bandgap modulation, induce a direct–indirect gap transition, and significantly modulate the effective mass of both electrons and holes in phosphorene, through changing bond lengths and bond angles under various strain conditions . Biaxial strain can tune the optical band gap of monolayer phosphorene by 1.5 eV and the exciton energy, which is useful in designing optoelectronics .…”
Section: Mechanical Properties and Strain Engineering Of 2d Semicondumentioning
confidence: 99%